Disability, discrimination and equal opportunities : a comparative labour law study - Harmse-Truter, Laurentia (University of Johannesburg, 2012)
This study aims to investigate the different ways in which the position of people with disabilities can be addressed. Antidiscrimination legislation can play a very important role. Efforts to create equal opportunities must, however, not be limited to legislative initiatives and policy declarations. There is an urgent need for education and training of this minority group. 7 Systematic efforts to heighten public awareness of civil rights and in particular the recognition of the rights of the disabled community are imperative. This study aims to bring home the truth that "disability rights are an idea and ideal whose time has come. ,, When addressing the issue of disability discrimination (or for that matter any kind of discrimination) several principles need to be addressed, the most important being the following: The meaning of the concept of "equality" needs to be established. The fact that all people are equal, does not necessarily mean that all people must be treated the same. When speaking about disability discrimination one must know who forms part of the protected class. For that reason the first issue that must be addressed is the definition of "disability": This leads to the next question, namely which individuals should be protected by anti-discrimination laws and should they benefit from affirmative action measures? What is meant by the term "discrimination"? Is it at all permissible to distinguish between groups of people and, if so, when and which standards are to be applied? What role can anti-discrimination legislation fulfil in the struggle for equality? When dealing with anti-discrimination legislation, what is required in order to prove discrimination and what remedies must be available to an aggrieved party? Normally, in case of criminal action proof is required beyond reasonable doubt and in case of civil action on the balance of probabilities. 10 Civil action offers more effective remedies, but should it be punitive in nature (by awarding damages to the aggrieved party) or non-punitive (by putting the aggrieved party in his/her "rightful place")? What sort of enforcement mechanism is needed? Is it a task for the ordinary tribunals or rather a special body created for that purpose? What defences should be available to an employer accused of discriminatory practices? Who should benefit from enforcement? Only the individual victim or all members of that group? Is anti-discrimination legislation sufficient or is something in addition called for? If positive measures are required, what form must these measures take? This study will address these questions specifically with relation to people with disabilities.The "equality principle" will first be studied. Thereafter the concept of "disability" will be defined. There is a movement away from a medical model of disability towards a social model that takes account of the disabling effects of attitudes and structural barriers on the position of disabled people. Then the concept of "discrimination" will be addressed. Discrimination has many different forms and can take place in different contexts In the following chapter possible solutions to the problem of disability discrimination will be raised. Thereafter follows an important comparative analysis of different jurisdictions on international, supra-national and national level. Different jurisdictions have reached different stages in addressing this problem. The factual analysis of each jurisdiction will include the existence of any anti-discrimination legislative measures, the scope of the protected class, applicable employment provisions, defences available to employers, and the success achieved in addressing the problem. The contentious issue of affirmative action measures will also be addressed. By drawing inferences from the comparative study, suggestions will be made for future developments in South Africa. The conclusion is reached that it is imperative for South Africa to draft disability anti-discrimination legislation that takes account of the needs of this minority group. Legislative initiatives, however, are not enough and must be supported by various programmes aimed at the disabled themselves and the community that they live in. Only then can human rights become a reality also for people with disabilities.
Keywords: Comparative law; Discrimination; Employment; Labour law; People with disabilities